Will the Next Generation of PACS Be Sitting on a Cloud? - Philbin, James; Prior, Fred; Nagy, Paul (Journal of Digital Imaging, 2011)
Cloud computing has gathered significant attention from information technology (IT) vendors in providing massively scalable applications as well as highly managed remote services. What is cloud computing and how will it impact the medical IT market? Will the next generation of picture archiving and communication systems be leveraging cloud technology?